Anesthetic Management of a Severe Chronic Obstructive Pulmonary Disease Patient Undergoing Video-Assisted Thoracoscopic Surgery for Diaphragmatic Hernia Repair - Arisadika, Putu Bagus; Sinardja, Cynthia Dewi (PROMOTOR, 2025)
Chronic obstructive pulmonary disease (COPD) is a progressive respiratory disorder that increases the risk of perioperative complications, particularly in thoracic surgery requiring one-lung ventilation (OLV). Patients with severe COPD are prone to respiratory failure, which make the anesthetic management challenging, escpecially to prevent acute exacerbation. A 58-year-old female with severe COPD and acute exacerbation underwent video-assisted thoracoscopic surgery (VATS) for diaphragmatic hernia repair. Preoperative optimization included nebulization therapy, glucose control, and respiratory muscle training. General anesthesia was maintained with sevoflurane. Lung isolation achieved with placement of double-lumen tube. Midway through surgery, the patient developed acute respiratory distress, requiring manual ventilation with 100 oxygen and PEEP 5 cmH₂O, deepened anesthesia with sevoflurane 4 MAC, rocuronium 10 mg IV, and methylprednisolone 125 mg IV. After stabilization, mechanical ventilation was resumed with down titration of oxygen fraction, and the procedure was completed successfully. This case highlights the importance of perioperative planning in severe COPD, particularly the need for preoperative pulmonary optimization and intraoperative vigilance. Rapid recognition and intervention in acute exacerbations are crucial to preventing hypoxemia and ventilatory failure. The use of tailored ventilation strategies and bronchodilator therapy contributed to the successful management of this high-risk patient. Anesthetic management in severe COPD requires a multidisciplinary approach, including preoperative pulmonary preparation, intraoperative lung-protective ventilation, and immediate intervention during exacerbations. This case underscores the importance of individualized anesthetic strategies to optimize surgical outcomes in patients with compromised respiratory function.